Does Forgiveness Climate Contribute to Employee's Flourishing? A Case of Nigerian Hospitality Industry - Gbadebo, Adebanke Flora (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Forgiveness climate has been a thoroughly researched topic in the field of tourism, considering the direct/indirect significance of its effect on customer satisfaction. The perception of employees about the position accorded to forgiveness in the organization significantly affects how they execute their roles, the satisfaction they find in it and the speed with which they recover from their errors. Considering several studies, it has been found that employees tend to evaluate their working environment based on the reactions and relationship established between themselves, their colleagues and their employer as a crucial role player in determining their suitability within the job. It is noteworthy that such evaluations may determine if the employee flourishes in the job. In this thesis, considering the Nigerian hospitality industry as a case study, we have sought to investigate using empirical studies erected on 7 hypotheses, the effects of the forgiveness climate perceived by employees on their tendency and capability to flourish on the job and its environments. The hypotheses presented were validated in the study, indicating clearly that forgiveness leads to on-the-job satisfaction among employees within the Nigerian hospitality industry, as forgiveness expresses the capacity of the organizations to tolerate errors and mistakes in order to promote a better workforce. Thus, recommendations were made to promote employee flourishing within the industry. For the purpose of this study, 5 variables were considered namely forgiveness climate, service recovery performance, helping behaviour, employee satisfaction and employee flourishing. Keywords: Employee Flourishing; Satisfaction; Forgiveness; Forgiveness Climate.

ÖZ:Bağışlama iklimi, müşteri memnuniyeti üzerindeki etkisinin doğrudan veya dolaylı önemi düşünüldüğünde, Turizm alanında kapsamlı bir şekilde araştırılmış bir konudur. Çalışanların örgütteki affetmeye verilen pozisyon hakkındaki algısı, rollerini nasıl yerine getirdiklerini, içinde buldukları memnuniyeti ve hatalarından kurtulma hızlarını önemli ölçüde etkiler. Yapılan çeşitli araştırmalar incelendiğinde, çalışanların işlerine uygunluklarının belirlenmesinde önemli bir rol oyuncusu olarak çalışma ortamlarını kendileri, meslektaşları ve işverenleri arasında kurulan reaksiyonlara ve ilişkilere dayalı olarak değerlendirme eğiliminde oldukları tespit edilmiştir. Dikkate değer olan, bu tür değerlendirmelerin ve sonuçlarının, kök bulma yeteneğini belirleyen ve iş içinde bir çalışan olarak gelişen önemli unsurlara dönüşmesi olabilir. Bu tezde, Nijerya otelcilik endüstrisini bir analiz çalışması olarak ele alarak, 7 hipotez üzerine kurulan çalışmaları, çalışanların algıladıkları ikliminin, iş ve çevresi üzerinde gelişme eğilimleri ve yetenekleri üzerindeki etkilerini araştırmaya çalıştık. Sunulan hipotezler çalışmada doğrulandı ve affetmenin Nijerya otelcilik endüstrisindeki çalışanlar arasında iş başında tatmine yol açtığını, çünkü affetmenin kuruluşların daha iyi bir iş gücünü teşvik etmek için hataları ve yanlışları tolere etme kapasitesini ifade ettiğini gösteriyor. Böylece, çalışanların sektörde gelişmesini teşvik etmek için önerilerde bulunuldu. Bu çalışmanın amacı için affetme iklimi, hizmeti iyileştirme performansı, yardımcı davranış, çalışan memnuniyeti ve çalışan gelişimi olmak üzere 5 değişken ele alınmıştır. Anahtar Kelimeler: Çalışan Gelişimi; Memnuniyeti; Bağışlama; Affetme Iklimi.
Master of Science in Tourism Management. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Tourism, 2020. Supervisor: Supervisor: Prof. Dr. Turgay Avcı.
Keywords: Tourism-Hospitality Industry-Work Environment-Nigeria; Employee Motivation; Job satisfaction-Employee morale-Attitude (Psychology); Forgiveness Climate-Personnel Management; Employee Flourishing; Satisfaction; Forgiveness; Forgiveness Climate